Compression test of built-up sigma section cold-formed steel column with holes - Nurul Faizah, Muhammad Rusli (2019)
An experimental investigation was conducted to study the Compression test of built-up sigma section cold-formed steel Column holes and to determine the maximum compression load of sigma section Cold-Formed steel column. A total 8 specimen of steel column with holes and without holes and also thickness 1.2 and 2.0 mm were tested using universal testing machine (UTM). Typical applications include framing for windows, doorways, shear walls, and multi-story cold-formed steel framed buildings in which the lower floor utilizes built-up studs to carry the load. The built-up studs in this study consisted of eight Sigma sections oriented back-to-back forming an I-shaped crosssection. For each specimen, the studs were connected to each other with two self-drilling screws spaced at a set interval. A cold-formed steel track section was connected running perpendicular to each end of the built-up stud with a single self-drilling screw through each of the sigma sections. The purpose of the column section was to keep the ends of the studs together and represents a common end attachment. As a result of the investigation, the maximum compression load was shown and the mode of failure of coldformed steel column with the various position of holes.